Iron oxide magnetic powder dispersion slurry and its manufacturing method
By employing a quaternary ammonium salt and an organic acid with multiple carboxy groups as dispersants, the pH of the iron-based oxide magnetic powder dispersion slurry is reduced, addressing the issue of resin decomposition and enabling the use of a wider range of resins in magnetic recording media.
Patent Information
- Application Number
- JP2020152155
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-10
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2040-09-10
AI Technical Summary
Existing iron-based oxide magnetic powder dispersion slurries for magnetic recording media have high pH levels, which can cause resin decomposition when mixed with certain resins, limiting the variety of resins that can be used.
The use of a quaternary ammonium salt as a first dispersant and an organic acid with two or more carboxy groups, along with a polyvalent carboxylic acid, as a second dispersant to adjust the pH of the slurry to less than 11, while maintaining excellent dispersibility of the ε-type iron-based oxide particles.
This approach allows for the production of an iron-based oxide magnetic powder dispersion slurry with a small average secondary particle size of 65 nm or less and a low pH, enhancing the compatibility with various resins and improving the manufacturing process efficiency.
Smart Images

Figure 0007649120000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an iron-based oxide magnetic powder suitable for high-density magnetic recording media, radio wave absorbers, etc., and in particular to an iron-based oxide magnetic powder dispersion slurry having an average particle size on the order of nanometers, and a method for producing the same. [Background technology]
[0002] ε-Fe2O3 is an extremely rare phase among iron oxides, but nanometer-sized particles have a thermal conductivity of 20 kOe (1.59 × 10 6 Since ε-Fe2O3 exhibits a huge coercive force (Hc) of about 10 ... Meanwhile, in the field of magnetic recording, magnetic recording media with a high ratio of the reproduction signal level to particulate noise (C / N ratio: Carrier to Noise Ratio) are being developed, and in order to increase the recording density, there is a demand for finer magnetic particles that make up the magnetic recording layer. However, in general, finer magnetic particles tend to deteriorate their environmental resistance and thermal stability, and there is concern that the magnetic properties of the magnetic particles may decrease under the usage or storage environment. Therefore, by replacing part of the Fe site of ε-Fe2O3 with other metals with excellent heat resistance, it is possible to obtain a magnetic recording medium with the general formula ε-A x B y Fe 2-x-y O3 or ε-A x B y C z Fe 2-x-y-zVarious partial substitution products of ε-Fe2O3 (where A is a divalent metal element such as Co, Ni, Mn, or Zn, B is a tetravalent metal element such as Ti, and C is a trivalent metal element such as In, Ga, or Al) have been developed that have reduced particle size, variable coercive force, and excellent environmental resistance and thermal stability (Patent Document 3).
[0003] Since ε-Fe2O3 is obtained as a stable phase with a size on the order of nanometers, a special method is required for its production. The above-mentioned Patent Documents 1 to 3 disclose a method for producing ε-Fe2O3 by using fine crystals of iron oxyhydroxide produced by a liquid phase method as a precursor, coating the precursor with silicon oxide by a sol-gel method, and then heat-treating the precursor. As the liquid phase method, a reverse micelle method using an organic solvent as a reaction medium and a method using only an aqueous solution as a reaction medium are disclosed. However, since the magnetic properties of ε-Fe2O3 or partially substituted ε-Fe2O3 obtained by these methods vary, it has been proposed to improve their magnetic properties by removing the silicon oxide coating after heat treatment and performing a classification process. For example, Patent Document 4 and Patent Document 5 disclose a technique of centrifuging ε-Fe2O3 or a partially substituted product of ε-Fe2O3 produced by the reverse micelle method in ultrapure water. The reason why ultrapure water is used as a dispersion medium is to reduce the ionic strength of the medium and increase the dispersibility of the slurry. However, since the partially substituted products of ε-Fe2O3 or ε-Fe2O3 do not inherently exhibit good dispersibility near neutrality, the classification methods disclosed in Patent Document 4 and Patent Document 5 require that the silicon oxide coating be left partially on the partially substituted products of ε-Fe2O3 or ε-Fe2O3 in order to obtain good dispersibility in the neutral range, and there is a problem that the silicon oxide coating must be removed again after classification.
[0004] As an improvement of the above-mentioned dispersion treatment method, Patent Document 6 discloses a technique in which NaOH is added to a slurry containing particles of ε-Fe2O3 or a partially substituted product of ε-Fe2O3 produced using an aqueous solvent, and the pH of the dispersion is adjusted to 10 to 11, and then classification treatment is performed. Furthermore, as an improvement of the technique disclosed in Patent Document 6, Patent Document 7 discloses a technique in which a tetraalkylammonium salt is used as a dispersant, and a slurry with a pH of 11 to 14 is classified to obtain an iron-based oxide magnetic powder with a small coefficient of variation of particle size. In this specification, ε-iron oxide and partial substitution products of ε-iron oxide in which part of the Fe sites are substituted with other metal elements may be collectively referred to as ε-type iron-based oxides. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2008-174405 A [Patent Document 2] International Publication No. 2008 / 029861 [Patent Document 3] International Publication No. 2008 / 149785 [Patent Document 4] JP 2008-063199 A [Patent Document 5] JP 2008-063201 A [Patent Document 6] JP 2016-174135 A [Patent Document 7] JP 2019-175539 A Summary of the Invention [Problem to be solved by the invention]
[0006] As described above, the application of ε-type iron oxide magnetic powder to magnetic recording media is being considered. The slurry in which the iron oxide magnetic powder obtained after the dispersion process is dispersed by the manufacturing method disclosed in Patent Document 7 has an average secondary particle diameter of ε-type iron oxide particles of 65 nm or less, which is excellent in dispersibility, and is suitable for use as a paint containing iron oxide magnetic powder required to form a magnetic layer constituting a magnetic recording medium. However, the obtained iron oxide magnetic powder dispersion slurry after the dispersion process has a high pH of 11 or more. When the pH is high like this, when the iron oxide magnetic powder dispersion slurry after the dispersion process is mixed with a resin to prepare a paint containing the above-mentioned iron oxide magnetic powder, there is a risk that the resin will decompose due to the high pH depending on the type of resin, and there is a problem that the resin that can be used is limited. For example, urethane resin, phenolic resin, etc. are known as resins that may decompose at a high pH of 11 or more. Therefore, in order to increase the variety of resins that can be mixed and used, a magnetic particle slurry containing ε-type iron oxide with a lower pH is required. To address this problem, the inventors added sulfuric acid to the iron-based oxide magnetic powder dispersion slurry after the dispersion treatment, which had a pH of 11 or more, to adjust the pH to near neutral. However, it was found that this resulted in a significant increase in the average secondary particle size measured with a dynamic light scattering particle size distribution measuring device. Thus, an iron-based oxide magnetic powder dispersion slurry that combines a small average secondary particle size and a low pH of less than 11 has not been obtained. In view of the above, an object of the present invention is to provide an ε-type iron-based oxide magnetic powder dispersion slurry having excellent dispersibility and a pH of less than 11, and a method for producing the same. [Means for solving the problem]
[0007] The present inventors have found that when a second dispersant is added to a slurry containing an ε-type iron-based oxide magnetic powder and a quaternary ammonium salt, preferably a tetraalkylammonium salt, a polycarboxylic acid having two or more carboxy groups in the molecule and one or two types of hydroxyl group and amino group in addition to the carboxy groups, the dispersibility of the slurry does not deteriorate even if the pH of the slurry is lowered, and have completed the present invention described below.
[0008] In order to solve the above problems, the present invention provides (1) Provided is an iron-based oxide powder dispersion slurry in which particles of ε-iron oxide or ε-iron oxide in which part of the Fe sites are substituted with other metal elements (ε-type iron-based oxide) are dispersed in an aqueous solution, the average secondary particle size (DLS average particle size) of the particles of ε-iron oxide or ε-iron oxide in which part of the Fe sites are substituted with other metal elements being 65 nm or less as measured with a dynamic light scattering particle size distribution analyzer, and the pH at 25°C being 4 or more and less than 11. (2) The ratio of the DLS average particle size to the TEM average particle size of the ε-type iron-based oxide particles measured with a transmission electron microscope (DLS average particle size / TEM average particle size) is preferably 4 or less. (3) The ε-type iron-based oxide particles preferably have a TEM average particle size of 8 nm or more and 30 nm or less. (4) The iron-based oxide powder dispersion slurry of the above item (1) preferably contains a quaternary ammonium salt and an organic acid having two or more carboxyl groups in the molecule, and a polycarboxylic acid having one or two of a hydroxyl group and an amino group in addition to the carboxyl groups. (5) Furthermore, the quaternary ammonium salt is preferably a tetraalkylammonium salt.
[0009] (6) The present invention also provides a method for producing an iron-based oxide magnetic powder dispersion slurry, comprising the steps of: adding a first dispersant, which is a quaternary ammonium salt and an alkali, to a slurry containing ε-type iron-based oxide particles to obtain a slurry having a pH of 11 or more at 25° C.; and adding a second dispersant, which is an organic acid having two or more carboxy groups in the molecule and has one or two types of hydroxyl groups and amino groups in addition to the carboxy groups, to the slurry having a pH of 11 or more at 25° C., to adjust the pH of the slurry to less than 11 at 25° C. (7) In the iron-based oxide magnetic powder dispersion slurry having a pH of less than 11 at 25° C., the DLS average particle size of the ε-type iron-based oxide particles is preferably 65 nm or less. (8) The quaternary ammonium salt is preferably a tetraalkylammonium hydroxide. Effect of the Invention
[0010] By using the manufacturing method of the present invention, it is possible to obtain an iron-based oxide magnetic powder dispersion slurry having better dispersibility in a low pH range than before. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [Iron-based oxide magnetic powder] In the production method of the present invention, examples of the ε-type iron-based oxides that can be used as starting materials include the following. Represented by the general formula ε-Fe2O3, it does not contain any substitution elements. General formula ε-C z Fe 2-z Represented by O3 (where C is a trivalent metallic element). General formula ε-A x B y Fe 2-x-y O3 (where A is a divalent metal element and B is a tetravalent metal element). General formula ε-A x C z Fe 2-x-z It is represented as O3 (where A is a divalent metal element and C is a trivalent metal element). General formula ε-B y C z Fe 2-y-z O3 (where B is a tetravalent metal element and C is a trivalent metal element). General formula ε-A x B y C z Fe 2-x-y-z O3 (where A is a divalent metal element, B is a tetravalent metal element, and C is a trivalent metal element).
[0012] Here, the type substituted only with the C element has the advantage that the coercive force of the magnetic particles can be arbitrarily controlled and it is easy to obtain the same space group as ε-Fe2O3, but it is slightly inferior in thermal stability. Therefore, it is preferable to substitute with the A or B element simultaneously. The type substituted with the two elements A and B has excellent thermal stability and can maintain a high coercive force of the magnetic particles at room temperature, but it is slightly difficult to obtain a single phase with the same space group as ε-Fe2O3. The three-element substitution type of A, B, and C has the best balance of the above-mentioned characteristics, and is excellent in heat resistance, ease of obtaining a single phase, and controllability of the coercive force, and is the most preferable. Examples of the substitution elements include Co, Ni, Mn, Zn, etc. for A, Ti, Sn, etc. for B, and In, Ga, Al, etc. for C. In the case of the three-element substitution type, from the viewpoint of the balance of practical characteristics, it is preferable that the metal elements substituting a part of the Fe sites are Ga, Co, and Ti.
[0013] The preferable ranges of the substitution amounts x, y, and z of the three-element substitution product are as follows. x and y can take any range of 0 < x < 1 and 0 < y < 1. However, considering magnetic recording applications, it is necessary to change the coercive force of the magnetic particles of the three-element substitution product to some extent from that of unsubstituted ε-Fe2O3. Therefore, it is preferable that 0.01 ≦ x ≦ 0.2 and 0.01 ≦ y ≦ 0.2. Similarly, z may be in the range of 0 < z < 1, but from the viewpoints of coercive force control and ease of obtaining a single phase, it is preferable that the range is 0 < z ≦ 0.5. In the production method of the present invention, the ε-type iron-based oxide used as a starting material can maintain a high coercive force at room temperature by appropriately adjusting the values of y or x and y. Furthermore, it is also possible to control the coercive force to a desired value by adjusting x, y, and z. In the iron-based oxide magnetic powder of the present invention, in addition to ε-type iron-based oxide crystals, α-type iron-based oxide, γ-type iron-based oxide, and Fe3O4 crystals may be present as impurities, and these are all referred to as the iron-based oxide magnetic powder.
[0014] [Average particle size] In the manufacturing method of the present invention, the magnetic particles of ε-type iron oxide used as a starting material are preferably fine enough that each particle has a single magnetic domain structure. The average particle size (TEM average particle size) measured by a transmission electron microscope is preferably 30 nm or less. However, if the average particle size is too small, the proportion of fine particles that do not contribute to the above-mentioned improvement of magnetic properties increases, and the magnetic properties per unit weight of magnetic particle powder deteriorates, so that the average particle size is preferably 8 nm or more. The ε-type iron oxide used as a starting material in the present invention may be prepared by any method, including the manufacturing methods described in Patent Documents 1 to 6. When the production method of the present invention is used, as described below, an iron-based oxide powder dispersion slurry having a pH of less than 11 at 25° C. and a DLS average particle size of 65 nm or less can be obtained, and the ratio of the DLS average particle size to the TEM average particle size (DLS average particle size / TEM average particle size) is preferably 4 or less. The lower limit of the DLS average particle size / TEM average particle size is 1. Since the magnetic properties of magnetic particles depend on the primary particle size of the magnetic particles, the above-mentioned classification process is performed to make the primary particle size of the magnetic particles uniform. If the DLS average particle size / TEM average particle size exceeds 4, the number of aggregated particles increases, making it difficult to separate particles with large primary particle sizes from secondary particles that have small primary particle sizes but have become large due to aggregation by classification. For this reason, it is preferable that the DLS average particle size / TEM average particle size is 4 or less.
[0015] [Slurry containing iron oxide powder] In the manufacturing method of the present invention, first, a slurry is prepared by dispersing ε-type iron-based oxide magnetic particles as a starting material in pure water. In this case, from the viewpoint of suppressing the aggregation of iron-based oxides and reducing impurities, it is preferable that the conductivity of the solvent constituting the slurry is ≦15 mS / m. When using a slurry containing ε-type iron-based oxide magnetic particles produced by a wet method and immediately after removing the silicon oxide coating in an alkaline solution as a starting material, it is preferable to wash the slurry with pure water until the conductivity of the solvent is ≦15 mS / m. Then, a quaternary ammonium salt is added to the slurry, and the pH of the slurry at 25° C. is adjusted to 11 to 14. Note that, as described later, when a hydroxide of a tetraalkylammonium salt is used as the quaternary ammonium salt, the pH of the slurry at 25° C. is in the above range even without adding another alkali. The pH values described in this specification are values measured using a glass electrode based on JIS Z8802, and are values measured using a pH meter calibrated with an appropriate buffer solution according to the pH range to be measured as a pH standard solution. The pH values described in this specification are values directly read at 25°C from a pH meter compensated by a temperature compensation electrode.
[0016] [Quaternary ammonium ion] Quaternary ammonium ions are ammonium ions (NH4 + ) are cations in which all four hydrogen atoms have been replaced by organic groups, and the substituents are usually alkyl groups or aryl groups. In the manufacturing method of the present invention, a quaternary ammonium ion is used as the first dispersant for the ε-type iron oxide magnetic particles, which is stable in a strong alkaline range and provides good dispersibility for the magnetic particles. Among the quaternary ammonium ions, it is preferable to use tetraalkylammonium ions, which are easily available industrially. Tetraalkylammonium ions are quaternary ammonium cations with the molecular formula NR4 +(R is any alkyl group). Tetraalkylammonium salts are completely dissociated salts, and tetraalkylammonium ions exist as stable ions in an alkaline aqueous solution, so in the manufacturing method of the present invention, they are used as a surface modifier to improve the dispersibility of ε-type iron oxides in the slurry. Sources of tetraalkylammonium ions include hydroxides, chlorides, bromides, etc., but since the hydroxides of tetraalkylammonium ions are themselves strong alkalis, adding them to the slurry brings the pH of the slurry at 25°C into the above-mentioned preferred pH range without the need to add other alkalis, so it is more preferable to use tetraalkylammonium hydroxide as a dispersant. The tetraalkylammonium salts include quaternary ammonium salts having the same alkyl group, such as tetramethylammonium salts, tetraethylammonium salts, tetrapropylammonium salts, and tetrabutylammonium salts, as well as quaternary ammonium salts having different alkyl groups. Any of these can be used, but it is preferable to use hydroxides such as tetramethylammonium hydroxide (tetramethylammonium hydroxide: TMAOH), tetraethylammonium hydroxide (tetraethylammonium hydroxide: TEAOH), tetrapropylammonium hydroxide (tetrapropylammonium hydroxide), and tetrabutylammonium hydroxide (tetrabutylammonium hydroxide). In addition, although not particularly limited in the present invention, the concentration of the tetraalkylammonium ion is preferably 0.009 mol / kg or more and 1.0 mol / kg or less in order to modify the surface of the ε-type iron-based oxide particles in the slurry and to increase the dispersibility. The concentration of the quaternary ammonium ion in the iron-based oxide magnetic powder dispersion slurry can be determined by ion chromatography.
[0017] [Second dispersant] The greatest technical feature of the present invention is to add, as a second dispersant, an organic acid having two or more carboxy groups in the molecule, and a polycarboxylic acid having one or two types of hydroxyl group and amino group in addition to the carboxyl group, to a slurry containing an iron-based oxide powder, the pH of which is adjusted to 11 to 14 at 25°C by adding the above-mentioned tetraalkylammonium salt, and to adjust the pH of the slurry to 4 to less than 11 at 25°C. When the organic compound, i.e., the second dispersant, is added, the dispersibility of the slurry is not impaired even if the pH of the slurry to which the tetraalkylammonium salt has been added is lowered to less than 11 at 25°C. Specific examples of the organic compound include citric acid, tartaric acid, malic acid, glutamic acid, aspartic acid, isocitric acid, hydroxycitric acid, hydroxyphthalic acid, hydroxyterephthalic acid, and 2-hydroxy-1,3,5-benzenetricarboxylic acid. The reason why the addition of the organic compound does not deteriorate the dispersibility of the slurry even when the pH of the slurry containing the tetraalkylammonium salt at 25°C is lowered to less than 11 is currently unclear, but the inventors speculate that the mechanism is as follows. In other words, it is believed that one of the ionized carboxyl groups binds to the surface of the magnetic iron oxide particle, while the other ionized carboxylic acid faces the outside of the particle, generating charge repulsion that improves dispersibility. Although the effects of hydroxyl and amino groups are unclear, they are believed to play a role in assisting the binding of carboxyl groups to the particle surface or assisting the carboxyl groups to face the outside of the particle. The reason why the pH of the slurry after the organic compound is added is less than 11 at 25°C is to prevent the resin from decomposing when the iron-based oxide magnetic powder dispersion slurry and the resin are mixed to prepare a coating material for forming a magnetic layer of a magnetic recording medium, even if a resin that is easily decomposed by strong alkali is used, and to increase the variety of resins that can be used when preparing the coating material. In addition, by making the pH of the slurry after the organic compound is added less than 11 at 25°C, it is not necessary to use expensive equipment specifications for the classification operation and solid-liquid separation treatment in consideration of damage caused by alkali, and there is also an advantage in terms of manufacturing costs. From the viewpoint of suppressing the increase in the cost of the equipment used for the classification operation and solid-liquid separation treatment, it is more preferable that the pH of the slurry after the organic compound is added is 10 or less at 25°C. In addition, if the pH of the slurry at 25°C is less than 4, dissolution of the ε-type oxide particles occurs, and damage to the equipment used for the classification operation and solid-liquid separation treatment increases again, which is not preferable. Although not particularly limited in the present invention, the concentration of the second dispersant is preferably 0.009 mol / kg or more and 1.0 mol / kg or less in order to enhance the dispersibility of the ε-type iron-based oxide powder in the obtained slurry. The concentration of the second dispersant in the iron-based oxide magnetic powder dispersion slurry can be quantified by ion chromatography. Since the organic compound is itself a carboxylic acid having multiple carboxy groups in the molecule, when it is added to a slurry containing a tetraalkylammonium salt, the pH of the slurry decreases. However, if necessary, the pH can be adjusted by adding another alkali or acid.
[0018] [Distributed processing] In the manufacturing method of the present invention, the iron-based oxide powder-containing slurry to which the first and second dispersants have been added and the pH has been adjusted may be subjected to a dispersion treatment. Here, the dispersion treatment is a treatment for loosening the agglomerates of the ε-type iron-based oxide contained in the iron-based oxide powder-containing slurry. As a dispersion treatment method, known methods such as dispersion using an ultrasonic disperser, grinding using media such as a bead mill, and stirring using a stirring blade, a shaker, or a shaker can be used. The dispersion treatment of the slurry containing the iron-based oxide powder is carried out until the DLS average particle diameter becomes 65 nm or less if the average secondary particle diameter (DLS average particle diameter) of the iron-based oxide powder measured by a dynamic light scattering particle size distribution measuring device exceeds 65 nm before the dispersion treatment.
[0019] [Classification and solid-liquid separation] The manufacturing method of the present invention is intended to obtain an iron-based oxide powder-containing slurry that has good dispersibility and a lower pH than conventional methods. In order to obtain iron-based oxide powder as a magnetic material, the iron-based oxide powder-containing slurry obtained by the present invention is further subjected to a classification operation and a solid-liquid separation operation. As the classification operation, a known wet classification method such as a centrifugation method can be adopted. Fine particles can be removed by removing the supernatant after centrifugation, and coarse particles can be removed by removing the precipitate after centrifugation. The gravitational acceleration during centrifugation is preferably 40,000 G or more. In addition, it is preferable to repeat the classification operation three or more times. After the classification operation, the iron-based oxide magnetic powder is recovered using a known solid-liquid separation means, washed with water if necessary, and then dried.
[0020] [Transmission electron microscope (TEM) observation] TEM observation of the ε-type iron-based oxide particles contained in the iron-based oxide magnetic powder dispersion slurry obtained by the manufacturing method of the present invention was carried out under the following conditions. JEM-1011 manufactured by JEOL Ltd. was used for TEM observation. For particle observation, TEM photographs taken at a magnification of 100,000 times were used (those after removing the silicon oxide coating were used). -Measurement of average particle size and particle size distribution- Digitizing was used to evaluate the TEM average particle size and particle size distribution. Mac-View Ver. 4.0 was used as the image processing software. When using this image processing software, the particle size of a particle is calculated as the length of the long side of the rectangle that circumscribes the particle and has the smallest area. More than 200 particles were measured. Among the particles shown on the transmission electron microscope photograph, the selection criteria for particles to be measured were as follows: [1] Particles with any part lying outside the field of view of the photograph will not be measured. [2] Particles that are clearly defined and isolated are measured. [3] Particles that are independent and can be measured as single particles will be measured, even if they deviate from the average particle shape. [4] When particles overlap but have a clear boundary between them and the overall shape of the particle can be determined, each particle is measured as a single particle. [5] Particles that overlap, have unclear boundaries, and whose overall shape cannot be determined are not measured as their shape cannot be determined. The number average particle size of the particles selected based on the above criteria was calculated, and this was taken as the average particle size of the ε-type iron oxide particles contained in the iron oxide magnetic powder dispersion slurry, as determined by TEM observation. In addition, the number percentage (%) of the particles with a particle size of 8 nm or less among the selected particles was calculated.
[0021] [DLS average particle size] The iron-based oxide magnetic powder dispersion slurry of the present invention is characterized by having a DLS average diameter of 65 nm or less. This DLS average diameter of 65 nm or less means that the iron-based oxide magnetic powder necessary for forming the magnetic layer constituting the magnetic recording medium has excellent dispersibility, and the iron-based oxide magnetic powder dispersion slurry of the present invention can be suitably used for applications of paint containing iron-based oxide magnetic powder for forming the magnetic layer of the magnetic recording medium. There is no particular provision for the lower limit of this DLS average diameter, but the DLS average diameter when the particles of the iron-based oxide magnetic powder contained in the slurry are completely separated into individual particles is considered to be the theoretical minimum value. In other words, the lower limit of the DLS average diameter can be considered to be the TEM average particle diameter of the iron-based oxide magnetic powder constituting the slurry. [DLS average particle size measurement] The DLS average particle size of the slurry containing ε-type iron-based oxide particles obtained by the production method of the present invention was measured by a dynamic light scattering particle size distribution measurement method under the following conditions. The dynamic light scattering particle size distribution analyzer used was manufactured by Otsuka Electronics Co., Ltd. (FPAR-1000K high sensitivity model), and the fiber probe used was a dilute system probe. The measurement conditions were: measurement time (seconds) 180 seconds, repetition count 1 time, and solvent setting Water. The analysis mode was the cumulant method.
[0022] [Composition analysis by inductively coupled plasma atomic emission spectrometry (ICP-AES)] The composition of the obtained ε-type iron-based oxide magnetic powder was analyzed using an Agilent Technologies ICP-720ES, with measurement wavelengths (nm) of Fe: 259.940 nm, Ga: 294.363 nm, Co: 230.786 nm, and Ti: 336.122 nm. EXAMPLES
[0023] [Example 1] <Preparation of a slurry containing ε-type iron-based oxide particles> 2689g of raw material solution was prepared with Fe(III) concentration of 1.300mol / kg, Ga(III) concentration of 0.133mol / kg, Co(II) concentration of 0.053mol / kg, Ti(IV) concentration of 0.038mol / kg, chloride ion concentration of 3.996mol / kg, and nitrate ion concentration of 0.556mol / kg. The molar ratio of metal ions in this raw material solution was Fe:Ga:Co:Ti=1.705:0.175:0.070:0.050. Next, 4500g of pure water was added to a 10L reaction vessel, and the liquid temperature was adjusted to 40°C while mechanically stirring with a stirring blade. Next, while continuing the stirring and maintaining the liquid temperature at 40°C, the raw material solution and 3.414mol / kg of aqueous ammonia solution were added simultaneously to the pure water, and then the liquid temperature was maintained at 40°C while stirring for 60 minutes to obtain a colloidal solution (Procedure 1). In this case, the raw material solution was added continuously at a rate of 11.2 g / min over 240 minutes, and the aqueous ammonia solution was added continuously at a rate of 11.2 g / min over 240 minutes. Next, 866 g of a citric acid solution with a citric acid concentration of 0.694 mol / kg was continuously added to the colloidal solution obtained in step 1 over a period of 60 minutes at 40°C, and then 560 g of an aqueous ammonia solution with a 12.994 mol / kg concentration was added all at once. The mixture was then held at 40°C for 10 minutes with stirring to obtain a slurry of precursor particles, which are intermediate products of iron-based oxides (step 2).
[0024] The precursor slurry obtained in step 2 was collected and washed using an ultrafiltration membrane with a UF molecular weight cutoff of 50,000 until the electrical conductivity of the filtrate was 30 mS / m or less, to obtain a washed slurry (step 3). This washing was performed using a cross-flow method. The filtrate that passed through the filtration membrane was discharged, and the slurry that did not pass through the filtration membrane was replenished with pure water while filtering, and the amount of pure water replenished during washing was adjusted so that the total metal concentration of Fe, Ga, Co, and Ti in the resulting washed slurry was 0.685 mol / kg (step 3). After that, 1650g of the washed slurry obtained in step 3 was taken, and while stirring the taken slurry, 2050g of ethanol was added to adjust the temperature to 40°C, and 971g of 12.994mol / kg ammonia aqueous solution and 3870g of tetraethoxysilane (TEOS) as a silicon compound having a hydrolyzable group were added over 35 minutes. After that, the liquid temperature was kept at 40°C and stirring was continued for 1 hour, and the precursor was coated with the hydrolysis product of the silicon compound. The obtained slurry was then washed and separated into solid and liquid, and collected as a cake (step 4).
[0025] After drying the cake obtained in step 4 (precursor coated with gel-like hydrolysis product of silicon compound), the dried powder was heat-treated in a furnace in an air atmosphere at 1070°C for 4 hours to obtain ε-iron oxide powder in which some of the Fe sites coated with silicon oxide were replaced with other metal elements. Note that the hydrolysis product of silicon compound is converted to oxide when heat-treated in an air atmosphere (step 5). The ε-iron oxide powder obtained in step 5, in which some of the Fe sites covered with silicon oxide were replaced with other metal elements, was stirred in a 20 mass% NaOH aqueous solution at approximately 80°C for 20 hours to remove the silicon oxide from the particle surfaces, thereby obtaining a slurry containing ε-type iron-based oxide particles (step 6).
[0026] The slurry obtained in step 6 was washed with pure water until the electrical conductivity was ≦1 mS / m, thereby obtaining a washed slurry according to Example 1 (step 7). The washed slurry obtained in step 7 had a DLS average particle size of 135 nm and a pH of 8.7 at 25° C. The washed slurry obtained in step 7 was dispersed in pure water for 10 minutes at a frequency of 35 kHz using an ultrasonic disperser (UT-105, manufactured by SHARP Corporation) to adjust the slurry concentration, and the prepared slurry was dropped onto a collodion film on a grid to adhere thereto, and after natural drying, carbon deposition was performed and the slurry was subjected to TEM observation. As a result of measuring 200 particles by TEM observation, the TEM average particle size of ε-type iron-based oxide particles was 15.0 nm, and the number ratio of particles having a particle size of 8 nm or less was 3.0%. In addition, the obtained slurry was dried at 110° C. to obtain a powder, and a composition analysis was performed to calculate the molar composition ratio of each metal element when the total amount of iron and substituted metal elements was 2 moles. As a result, the molar ratio of metal ions in the obtained powder was Fe:Ga:Co:Ti=1.75:0.15:0.05:0.05. In the examples and comparative examples described in this specification, the slurry containing ε-type iron-based oxide particles obtained by the above steps up to step 7 is used as a starting material.
[0027] <Production of iron oxide magnetic powder dispersion slurry> To the post-wash slurry according to Example 1, a 35% by mass aqueous solution of tetraethylammonium hydroxide (TEAOH) was added as a first dispersant and stirred, and then the mixture was dispersed for 1 hour using an ultrasonic disperser (Yamato Scientific Co., Ltd., Yamato 5510) at a frequency of 40 kHz to prepare an alkaline iron-based oxide magnetic powder dispersion slurry (step 8). Note that TEAOH is a quaternary ammonium salt. The amount of the TEAOH aqueous solution added was such that the TEAOH concentration in the slurry obtained in step 8 was 0.099 mol / kg. The pH of the slurry obtained in step 8 at 25°C was 13.0, and the DLS average particle size was 30 nm. To the slurry obtained in step 8, a 20% by mass aqueous solution of citric acid was added as a second dispersant so that the pH at 25°C was 7.0, and the mixture was stirred, and then dispersed using an ultrasonic disperser to obtain an iron-based oxide magnetic powder dispersion slurry according to Example 1 (step 9). Citric acid has three carboxy groups in its molecular structure, and has a hydroxy group in addition to the carboxy groups. The DLS average particle size of the iron-based oxide magnetic powder dispersion slurry obtained in step 9 was measured and found to be 26 nm. In addition, the TEM average particle size of the ε-type iron-based oxide particles contained in the iron-based oxide magnetic powder dispersion slurry obtained in step 9 was measured in the same manner as for the slurry obtained in step 7, and the result was 16.1 nm. From the above, the ratio of the TEM average particle size to the DLS average particle size of the slurry obtained in step 9, DLS average particle size / TEM average particle size, was calculated to be 1.6. From the above results, it is found that an iron-based oxide magnetic powder dispersion slurry having a small DLS average particle size of 26 nm and a low pH of 7.0 at 25° C. can be obtained by adding a quaternary ammonium salt as a first dispersant to a slurry containing ε-iron oxide or ε-iron oxide particles in which a part of the Fe site is substituted with another metal element, adjusting the pH at 25° C. to 11 or more, and then adding a compound having two or more carboxy groups and one or two types of hydroxyl groups and amino groups bonded to carbon not constituting a carboxy group as a second dispersant, and adjusting the pH at 25° C. to 7.0. The iron-based oxide magnetic powder dispersion slurry having a small DLS average particle size and a low pH as described above can prevent the resin from decomposing when the iron-based oxide magnetic powder dispersion slurry and resin are mixed to prepare a paint for forming a magnetic layer of a magnetic recording medium, even when resins such as urethane resin and phenol resin that are easily decomposed by strong alkali are used, and the variety of resins that can be used in preparing the paint can be increased, making it suitable for use in magnetic recording media.
[0028] <Classification of ε-type iron oxide particles contained in iron oxide magnetic powder dispersion slurry> 40 g of the iron-based oxide magnetic powder dispersion slurry according to Example 1 obtained in step 9 was centrifuged for 30 minutes at a rotation speed of 18,000 rpm in an R20A2 rotor of a centrifuge (Hitachi Koki Co., Ltd., himac CR21GII), and 30 g of the supernatant slurry was collected. The centrifugal acceleration in the centrifugation was 39,000 G. The operation of adding 30 g of 1.5 mass % TEAOH aqueous solution to the slurry on the precipitation side, ultrasonic dispersion, centrifuging for 30 minutes at 18,000 rpm and 39,000 G, and removing 30 g of the supernatant slurry was repeated nine times (step 10). The number ratio of particles with a particle diameter of 8 nm or less in the ε-type iron-based oxide particles contained in the precipitation side slurry obtained in step 10 was 1.5% by TEM observation, and it was confirmed that the number ratio of particles with a particle diameter of 8 nm or less was reduced compared to the slurry obtained in step 7. This shows that, by adding the first and second dispersants, an iron-based oxide magnetic powder dispersion slurry having a small DLS average particle size of 65 nm or less can be obtained in the low pH range of less than 11 at 25°C, and as a result, a classification operation can be performed using a centrifuge in the low pH range of less than 11 at 25°C, and the proportion of particles 8 nm or less can be reduced. The above-mentioned slurry preparation conditions according to Example 1 and the physical properties of the obtained slurry are summarized in Table 1. Table 1 also shows the concentrations of the first dispersant and the second dispersant in the obtained iron-based oxide magnetic powder dispersion slurry. Here, the first dispersant concentration (mol / kg) in this example indicates the number of moles of TEAOH contained in 1 kg of the iron-based oxide magnetic powder dispersion slurry, and the second dispersant concentration (mol / kg) in this example indicates the number of moles of citric acid contained in 1 kg of the iron-based oxide magnetic powder dispersion slurry. Table 1 also shows these values for other examples and comparative examples.
[0029] [Example 2] An iron-based oxide magnetic powder dispersion slurry according to Example 2 was obtained by the same procedure as in Example 1, except that a 20% by mass tartaric acid aqueous solution was added instead of the citric acid aqueous solution as the second dispersant. Tartaric acid has two carboxy groups in its molecular structure, and a hydroxy group is bonded to the carbon that does not constitute the carboxy group. The DLS average particle size of the obtained slurry was 36 nm. The TEM average particle size of the ε-type iron-based oxide particles contained in the obtained slurry was 15.5 nm. The ratio of the TEM average particle size to the DLS average particle size of the iron-based oxide magnetic powder dispersion slurry according to Example 2, DLS average particle size / TEM average particle size, was calculated to be 2.3.
[0030] [Example 3] The iron-based oxide magnetic powder dispersion slurry according to Example 3 was obtained by the same procedure as in Example 1, except that a 20% by mass aqueous malic acid solution was added instead of the citric acid aqueous solution as the second dispersant. Note that malic acid has two carboxy groups in its molecular structure, and has hydroxy groups in addition to the carboxy groups. The DLS average particle size of the obtained iron-based oxide magnetic powder dispersion slurry was 42 nm. The TEM average particle size of the ε-type iron-based oxide particles contained in the obtained iron-based oxide magnetic powder dispersion slurry was 16.0 nm. The ratio of the TEM average particle size to the DLS average particle size of the iron-based oxide magnetic powder dispersion slurry according to Example 3, DLS average particle size / TEM average particle size, was calculated to be 2.6.
[0031] [Example 4] The iron-based oxide magnetic powder dispersion slurry according to Example 4 was obtained by the same procedure as in Example 1, except that L-glutamic acid powder was added as a second dispersant instead of the citric acid aqueous solution, and the second dispersant was added so that the pH at 250 ° C. was 8.9. Note that L-glutamic acid has two carboxy groups in its molecular structure, and has an amino group in addition to the carboxy groups. The DLS average particle size of the obtained slurry was 25 nm. The TEM average particle size of the ε-type iron-based oxide particles contained in the obtained iron-based oxide magnetic powder dispersion slurry was 14.2 nm. The ratio of the TEM average particle size to the DLS average particle size of the iron-based oxide magnetic powder dispersion slurry according to Example 4, DLS average particle size / TEM average particle size, was calculated to be 1.8.
[0032] [Example 5] An iron-based oxide magnetic powder dispersion slurry according to Example 5 was obtained by the same procedure as in Example 1, except that in step 9 of Example 1, an aqueous citric acid solution was added so that the pH at 25°C was 4.0. The DLS average particle size of the obtained slurry was 35 nm. The TEM average particle size of the ε-type iron-based oxide particles contained in the obtained slurry was 16.0 nm. The ratio of the TEM average particle size to the DLS average particle size of the iron-based oxide magnetic powder dispersion slurry according to Example 5, DLS average particle size / TEM average particle size, was calculated to be 2.2.
[0033] [Comparative Example 1] The slurry having a pH of 13.0 at 25°C obtained up to step 8 of Example 1 is defined as the iron-based oxide magnetic powder dispersion slurry according to Comparative Example 1. The DLS average particle size of the obtained slurry was 30 nm. The TEM average particle size of the ε-type iron-based oxide particles contained in the obtained slurry was 15.0 nm. The ratio of the TEM average particle size to the DLS average particle size of the iron-based oxide magnetic powder dispersion slurry according to Comparative Example 1, DLS average particle size / TEM average particle size, was calculated to be 2.0. The iron-based oxide magnetic powder dispersion slurry of Comparative Example 1 satisfies the conditions of claims 1 and 2 of the present application in terms of DLS average particle diameter and DLS average particle diameter / TEM average particle diameter. However, since the pH of the slurry at 25° C. is high at 13.0, it is necessary to use expensive equipment in consideration of damage to equipment used in classification operations and solid-liquid separation treatment, and there is a significant disadvantage in terms of production costs. Furthermore, there is a risk of resin decomposition when mixed with a resin that decomposes at a high alkaline pH, and therefore the slurry is not suitable for use as a coating material containing magnetic particles for forming a magnetic layer that constitutes a magnetic recording medium.
[0034] [Comparative Example 2] A 20% by mass NaOH aqueous solution was added to the slurry obtained in step 7 of Example 1 so that the pH at 25° C. was 13.1, and the mixture was stirred, and then dispersed using an ultrasonic disperser to prepare a slurry. The DLS average particle size was 139 nm. A 20% by mass aqueous citric acid solution was added as a dispersant to the obtained slurry so that the pH at 25°C was 7.0, and the mixture was stirred, and then dispersed using an ultrasonic disperser to obtain an iron-based oxide magnetic powder dispersion slurry according to Comparative Example 2. The DLS average particle size of the obtained slurry was 145 nm. The TEM average particle size of the ε-type iron-based oxide particles contained in the obtained slurry was 15.6 nm. The ratio of the TEM average particle size to the DLS average particle size of the iron-based oxide magnetic powder dispersion slurry according to Comparative Example 2, DLS average particle size / TEM average particle size, was calculated to be 9.3. These results show that when the pH at 25°C of a slurry containing ε-type iron-based oxide particles is adjusted to 11 or more without adding a quaternary ammonium salt as a first dispersant, it is not possible to obtain an alkaline iron-based oxide magnetic powder dispersion slurry with a small DLS average particle size of 65 nm or less, and furthermore, even if a second dispersant, a compound having two or more carboxy groups and a hydroxy group in addition to the carboxy groups, is added to the slurry, it is not possible to obtain an iron-based oxide magnetic powder dispersion slurry with a DLS average particle size of 65 nm or less.
[0035] [Comparative Example 3] An iron-based oxide magnetic powder dispersion slurry according to Comparative Example 3 was obtained by the same procedure as in Example 1, except that in step 9 of Example 1, a 10 mass% sulfuric acid aqueous solution was added instead of the citric acid aqueous solution. The DLS average particle size of the obtained slurry was 2432 nm. The TEM average particle size of the ε-type iron-based oxide particles contained in the obtained slurry was 14.7 nm. The ratio of the TEM average particle size to the DLS average particle size of the iron-based oxide magnetic powder dispersion slurry according to Comparative Example 3, DLS average particle size / TEM average particle size, was calculated to be 165.4. These results show that if the pH of a slurry containing ε-type iron-based oxide particles to which a quaternary ammonium salt has been added is simply adjusted to less than 11 at 25°C without adding a second dispersant, a compound having two or more carboxy groups and one or two types of hydroxyl groups and amino groups in addition to carboxy groups, it is not possible to obtain an iron-based oxide magnetic powder dispersion slurry with a DLS average particle size of 65 nm or less.
[0036] [Comparative Example 4] An iron-based oxide magnetic powder dispersion slurry according to Comparative Example 4 was obtained by the same procedure as in Example 1, except that in step 9 of Example 1, a 20 mass% lactic acid aqueous solution was added instead of the citric acid aqueous solution. The DLS average particle size of the obtained slurry was 1092 nm. The TEM average particle size of the ε-type iron-based oxide particles contained in the obtained slurry was 14.8 nm. The ratio of the TEM average particle size to the DLS average particle size of the iron-based oxide magnetic powder dispersion slurry according to Comparative Example 4, DLS average particle size / TEM average particle size, was calculated to be 73.8. These results show that even if a compound having only one carboxy group in its molecule is added to a slurry containing ε-type iron-based oxide particles to which a quaternary ammonium salt has been added, and then the pH of the slurry at 25°C is adjusted to less than 11, it is not possible to obtain an iron-based oxide magnetic powder dispersion slurry with a DLS average particle size of 65 nm or less.
[0037] [Comparative Example 5] In step 9 of Example 1, a 20% by mass 1,2,3-propanetricarboxylic acid aqueous solution was added instead of the citric acid aqueous solution, and the procedure was the same as in Example 1 to obtain an iron-based oxide magnetic powder dispersion slurry according to Comparative Example 5. Note that 1,2,3-propanetricarboxylic acid is a tricarboxylic acid having three carboxy groups in its molecular structure, but has neither a hydroxy group nor an amino group in its molecule. The DLS average particle size of the obtained slurry was 496 nm. The TEM average particle size of the ε-type iron-based oxide particles contained in the obtained slurry was 15.4 nm. The ratio of the TEM average particle size to the DLS average particle size of the iron-based oxide magnetic powder dispersion slurry according to Comparative Example 5, DLS average particle size / TEM average particle size, was calculated to be 32.2. These results show that when a compound having two or more carboxy groups in its molecular structure and no hydroxyl groups or amino groups other than the carboxy groups is added to a slurry containing ε-type iron-based oxide particles to which a quaternary ammonium salt has been added, and the pH at 25°C is adjusted to less than 11, it is not possible to obtain an iron-based oxide magnetic powder dispersion slurry with a DLS average particle size of 65 nm or less.
[0038] [Comparative Example 6] 20% by weight of citric acid was added dropwise to a 0.099 mol / kg TEAOH aqueous solution so that the pH at 25° C. was adjusted to 7.0, and the solution was stirred to obtain a TEAOH-citric acid mixture. 80 g of the TEAOH-citric acid mixture was added to 20 g of the slurry obtained in step 7 of Example 1, and the mixture was stirred, and then dispersed using an ultrasonic disperser to obtain an iron-based oxide magnetic powder dispersion slurry according to Comparative Example 6. The DLS average particle size of the obtained slurry was 130 nm, and the pH at 25° C. was 7.7. The TEM average particle size of the ε-type iron-based oxide particles contained in the obtained slurry was 16.2 nm. The ratio of the TEM average particle size to the DLS average particle size of the iron-based oxide magnetic powder dispersion slurry according to Comparative Example 6, DLS average particle size / TEM average particle size, was calculated to be 8.0. These results show that even if a quaternary ammonium salt and a compound having two or more carboxy groups and one or two types of hydroxyl groups and amino groups in addition to carboxy groups are added to a slurry containing ε-type iron-based oxide particles and the pH at 25°C is adjusted to less than 11, it is not possible to obtain an iron-based oxide magnetic powder dispersion slurry with a small DLS average particle size of 65 nm or less, without first adjusting the pH at 25°C to 11 or more by adding a quaternary ammonium salt.
[0039] [Table 1]
Claims
1. An iron-based oxide powder dispersion slurry in which particles of ε-iron oxide or ε-iron oxide in which part of the Fe sites are substituted with other metal elements are dispersed in an aqueous solution, the iron-based oxide powder dispersion slurry containing a quaternary ammonium salt and a polycarboxylic acid which is an organic acid having two or more carboxy groups in the molecule and has one or two types of hydroxyl group and amino group in addition to the carboxy groups, the average secondary particle diameter (hereinafter referred to as DLS average particle diameter) of the particles of ε-iron oxide or ε-iron oxide in which part of the Fe sites are substituted with other metal elements measured with a dynamic light scattering particle size distribution measuring device is 65 nm or less, and the iron-based oxide magnetic powder dispersion slurry has a pH of 4 or more and less than 11 at 25°C.
2. 2. The iron-based oxide magnetic powder dispersion slurry according to claim 1, wherein the ratio (DLS average particle size / TEM average particle size) of the DLS average particle size to the average particle size (hereinafter referred to as TEM average particle size) of ε-iron oxide particles or ε-iron oxide particles in which a portion of the Fe sites is substituted with other metal elements, measured by a transmission electron microscope, is 4 or less.
3. 2. The iron-based oxide magnetic powder dispersion slurry according to claim 1, wherein the TEM average particle size is 8 nm or more and 30 nm or less.
4. 2. The iron-based oxide magnetic powder dispersion slurry according to claim 1, wherein the quaternary ammonium salt is a tetraalkylammonium salt.
5. A step of adding a quaternary ammonium salt as a first dispersant and an alkali to a slurry containing particles of ε-iron oxide or ε-iron oxide in which a part of the Fe sites is substituted with another metal element, to obtain a dispersed slurry having a pH of 11 or more at 25° C.; a step of adding a second dispersant, which is an organic acid having two or more carboxy groups in the molecule and a polycarboxylic acid having one or two types of hydroxyl groups and amino groups in addition to the carboxy groups, to the iron-based oxide powder dispersion slurry having a pH of 11 or more at 25° C., and adjusting the pH of the slurry at 25° C. to less than 11; The method for producing an iron-based oxide magnetic powder dispersion slurry comprising the steps of:
6. 6. The method for producing an iron-based oxide magnetic powder dispersion slurry according to claim 5, wherein the DLS average particle size of the ε-iron oxide or the ε-iron oxide in which a part of the Fe site is substituted with another metal element in the iron-based oxide magnetic powder dispersion slurry is 65 nm or less.
7. 6. The method for producing an iron-based oxide magnetic powder dispersion slurry according to claim 5, wherein the quaternary ammonium salt is a tetraalkylammonium hydroxide.
Citation Information
Patent Citations
epsi-IRON OXIDE-BASED MAGNETIC MATERIAL
JP2008063199A
epsi-IRON OXIDE POWDER HAVING IMPROVED MAGNETIC PROPERTY
JP2008063201A
METHOD FOR PRODUCING epsilon-Fe2O3 CRYSTAL
JP2008174405A
Precursor of iron-based oxide magnetic particle powder and method for producing iron-based oxide magnetic particle powder using the same
JP2016098131A
Iron-based oxide magnetic particle powder and method for producing iron-based oxide magnetic particle powder
JP2016174135A